Fetal Gallstones in a Newborn after Maternal COVID-19 Infection - Gurleen Kaur Kahlon; Anna Zylak; Patrick Leblanc; Noah Kondamudi (Case Reports in Pediatrics)
Fetal gallstones are rare incidental findings on ultrasound during pregnancy. We describe a newborn girl with gallstones that was born to a mother who had COVID-19 infection during her last trimester. The baby remained asymptomatic, and the stones resolved spontaneously without any treatment or complications within six weeks of birth. Several conditions predispose to fetal gallstones, and it is unclear if the recent maternal COVID-19 infection had any role in the occurrence of these abnormalities or was merely coincidental. This is the first case describing an association of fetal gallstones with a COVID-19 infection in pregnancy.